2020
DOI: 10.1161/jaha.120.015927
|View full text |Cite
|
Sign up to set email alerts
|

Additional Low‐Voltage‐Area Ablation in Patients With Paroxysmal Atrial Fibrillation: Results of the Randomized Controlled VOLCANO Trial

Abstract: Background The efficacy of low‐voltage‐area ( LVA ) ablation has not been well determined. This study aimed to investigate the efficacy of LVA ablation in addition to pulmonary vein isolation on rhythm outcomes in patients with paroxysmal atrial fibrillation ( AF ). Methods and Results VOLCANO (Catheter Ablation Targeting Low‐Vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 15 publications
6
74
0
1
Order By: Relevance
“…As for the regions near the PVs, the regions of peak‐to‐peak electrogram <0.2 mV was defined as scarred regions, and scarred regions was excluded from LVAs to avoid measuring the scarred regions resulting from PV isolation. Similar to previous study, LVAs were defined as regions with ≥5 cm 2 low‐voltage points across the total surface area of the left atrium 10 . The target number of mapping points was ≥100 with the 3.5‐mm tip catheter and ≥1000 with the multielectrode mapping catheter throughout the left atrium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the regions near the PVs, the regions of peak‐to‐peak electrogram <0.2 mV was defined as scarred regions, and scarred regions was excluded from LVAs to avoid measuring the scarred regions resulting from PV isolation. Similar to previous study, LVAs were defined as regions with ≥5 cm 2 low‐voltage points across the total surface area of the left atrium 10 . The target number of mapping points was ≥100 with the 3.5‐mm tip catheter and ≥1000 with the multielectrode mapping catheter throughout the left atrium.…”
Section: Methodsmentioning
confidence: 99%
“…low-voltage points across the total surface area of the left atrium. 10 The target number of mapping points was ≥100 with the 3.5-mm tip catheter and ≥1000 with the multielectrode mapping catheter throughout the left atrium. All analyses were performed using commercial software (SPSS, SPSS, Inc.).…”
Section: Voltage Mappingmentioning
confidence: 99%
“…1,4 VOLCANO was a randomized controlled trial that compared 1-year AF recurrence rates between following ablation strategies: PVI alone for patients without LVAs, PVI plus LVA ablation for those with LVAs, and PVI alone for those with LVAs. 5 Results showed that poorer rhythm outcomes in patients with LVAs than those without. In addition, comparable AF recurrence rates were observed between patients with and without LVA ablation, suggesting that LVA ablation in addition to PVI had no beneficial impact on 1-year rhythm outcomes in paroxysmal AF patients.…”
Section: Introductionmentioning
confidence: 96%
“…Patients with low-voltage areas had a signifi cantly higher recurrence rate. Interestingly, one of the factors associated with recurrence in patients with low voltage areas was their larger area -in the group with recurrence it was on average 20  15.9 cm 2 , and in the group without recurrence -13.3  8.7 cm 2 , p = 0.01 [22]. In our group, regardless of recurrence, the abnormal area was about 15 cm 2 , closely similar to that of non-recurrent patients in VOLCANO, and this, combined with our relatively small number of patients, may explain ненадващата на пръв поглед липса на корелация между абнормната площ и рецидивите.…”
mentioning
confidence: 99%
“…Пациентите с нисковолтажни зони са имали сигнификантно по-голяма честота на рецидиви. Интересно е, че един от факторите, свързани с рецидиви при лицата с нисковолтажни зони, е по-голямата им площ -в групата с рецидиви тя е била средно 20 ± 15.9 cm 2 , а в групата без рецидив -13.3 ± 8.7 cm 2 , р = 0.01 [22]. В нашата група, независимо от рецидивите, абнормната площ е около 15 cm 2 , много близка до тази на пациентите без рецидив във VOLCANO, и това, в съчетание със сравнително малкия ни брой пациенти, може би обяснява из-LA dilation, but still other ultrasound parameters such as the LA area or volume have been used in grading its severity.…”
unclassified